Integrating Ethnomathematics into Mathematics Learning: Effects on Students' Critical Thinking Skills, Self-Efficacy, and Learning Motivation - Nuryadi, Nuryadi; Juwandi, Juwandi; Rumasoreng, Muhammad Irfan; Taufik, Muhammad (Berkala Ilmiah Pendidikan, 2025)
This study examines the effects of learning motivation and mathematical self-efficacy on students' critical thinking skills in an ethnomathematics-based learning context. A quantitative correlational design was employed. The sample consisted of 34 eighth-grade students selected through simple random sampling. Data were collected using a learning motivation questionnaire, a mathematical self-efficacy questionnaire, and a critical thinking test designed based on culturally contextualized mathematical problems. Data were analyzed using regression and path analysis. The results show that mathematical self-efficacy has a significant positive effect on students' critical thinking skills (β = 0.550, p < 0.05), while learning motivation does not have a significant direct effect (β = 0.237, p > 0.05). Simultaneously, learning motivation and self-efficacy significantly influence critical thinking skills, with a coefficient of determination of 0.464. This indicates that these variables can explain 46.4% of the variance in critical thinking skills within an ethnomathematics-based learning environment. These findings suggest that students' confidence in their mathematical abilities plays a more dominant role than motivation in supporting critical thinking, particularly when engaging with culturally contextualized mathematical tasks. Ethnomathematics-based learning provides meaningful contexts that enhance engagement; however, its effectiveness in fostering higher-order thinking depends largely on students' self-efficacy. This study highlights the importance of integrating culturally responsive approaches in mathematics education while simultaneously strengthening students' self-efficacy to optimize the development of critical thinking.